The Role of Administrative Law in Environmental Protection (Journal of human and social sciences, 2015)
This paper examines the role of administrative law in environmental protection through regulatory mechanisms, with a focus on Libyan legislation. The study discusses the evolution of environmental protection concepts and pollution, highlighting the administration's role in maintaining public order (health, tranquility, security). It also addresses the legal and procedural means used by administrative bodies to tackle environmental challenges.
Keywords: Administrative Law; Environmental Protection; Libyan Legislation; Administrative Control; Public Order